Dual Antibiotic Prophylaxis in Total Knee Arthroplasty: Where Do We Stand? - Villa, Jesus M.; Pannu, Tejbir S.; Riesgo, Aldo M.; Patel, Preetesh D.; Mont, Michael A.; Higuera-Rueda, Carlos A. (The Journal of Knee Surgery, 2020)
The risk of surgical site infection in primary total knee arthroplasty (TKA) has been reduced with the use of prophylactic antibiotics. First or second generation cephalosporins are still recommended as the primary prophylactic choice, but with the rise in the incidence of methicillin-resistant Staphylococcus aureus (MRSA) infections, evidence has emerged in favor of using dual antibiotics including vancomycin. However, it is unclear whether these combinations of antibiotic regimens further reduce postoperative infection rates. As a result, the objective of this review is to summarize the current literature concerning the use of dual prophylactic antibiotics in TKA. The most common dual prophylactic antibiotic combination is cefazolin (C) and vancomycin (V). In general, when comparing the effectiveness of single versus dual antibiotics, conflicting results have been reported. Three studies demonstrated no substantial decrease in overall postoperative infection rates with the use of dual antibiotics when compared with cefazolin alone. One found a significant decrease only in MRSA infection rates when using cefazolin and vancomycin (CV) (0.8% C alone vs. 0.08% CV, p < 0.05). Another investigation evaluated revision TKA patients who had combined cefazolin and vancomycin prophylaxis and showed a significant decline in both overall infection (7.89% [C] vs. 3.13% [CV]) and MRSA infection rates (4.21% [C] vs. 0.89% [CV]; p < 0.05). Concerning the safety profile of dual antibiotics, particular precautions must be adopted with the use of vancomycin because of the risk of acute kidney injury. Instead of vancomycin, an alternate less nephrotoxic antibiotic option might be teicoplanin. Unfortunately, this latter agent is only available outside of the United States. In conclusion, the value of dual antibiotic prophylaxis for the prevention of periprosthetic knee infections remains unclear primarily because all comparative studies performed between dual and single antibiotics have been of low evidence with retrospective designs. Larger multicenter randomized controlled trials are warranted.
Keywords: dual prophylactic antibiotics; total knee arthroplasty; cefazolin and vancomycin; periprosthetic joint infection; periprosthetic joint infection